Bacteriocins From LAB and Other Alternative Approaches for the Control of Clostridium and Clostridiodes Related Gastrointestinal Colitis - Todorov, Svetoslav D.; Kang, Hye-Ji; Ivanova, Iskra V.; Holzapfel, Wilhelm H. (Frontiers in Bioengineering and Biotechnology, 2020)
The gut microbiome is considered as a promising target for future non-conventional therapeutic treatment of inflammatory and infectious diseases. The search for appropriate safe and beneficial (lactic acid bacterial and other) putative probiotic strains and/or their antimicrobial metabolites represents a challenging approach for combating several problematic and emerging infections. The process of selecting suitable strains, especially of lactic acid bacteria (LAB) with superior properties, has been accelerated and intensified during the past two decades, also thanks to recent developments in lab techniques. Currently, special focus is on the potential of antimicrobial metabolites produced by some LAB strains and their application as active therapeutic agents. The vision is to develop a scientific basis for ‘biotherapeutics’ as alternative to conventional approaches in both human and veterinary medicine. Consequently, innovative and promising applications of LAB to the therapeutic practice are presently emerging. An overview of the existing literature indicates that some antimicrobial metabolites such as bacteriocins, widely produced by different bacterial species including LAB, are promising biotherapeutic agents for controlling infections caused by potential pathogens such as Clostridium and Clostridiodes. Non-conventional, safe and well designed therapeutic treatments may contribute to the improvement of gut dysbiotic conditions. Thereby gut homeostasis can be restored and infammatory conditions such as gastrointestinal colitis ameliorated. Combining the knowledge on the production, characterization and application of bacteriocins from probiotic LAB, together with their antibacterial properties, appears to be a promising and novel approach in biotherapy. In this overview, different scenarios for the control of Clostridium spp. by application of bacteriocins as therapeutic agents, also in synergistic combination with antibiotics, will be discussed.